PENGALAMAN KOMUNIKASI PARA PENYINTAS COVID-19 DI LINGKUNGAN TEMPAT TINGGAL - Tasya Khairina Isnaini (2021)
Living in the Corona pandemic with the increasing number of positive cases of COVID-19 in Indonesia from time to time creates fear and worry for the people. This is what ultimately rising the stigma among the community towards COVID-19 patients and survivors in the environment where they live. This research is intended to explore and also describe what experiences have been experienced by COVID-19 survivors in their environment since before being declared positive for Corona until being declared cured. This research was done since october 2020 to july 2021 in Bekasi City, West Java. Qualitative - interpretative is used as the approach, while phenomenology is used as the method. Data mining was carried out by means of in-depth interviews about the communication experiences of 10 COVID-19 survivors who were used as informants. The results of this study indicate that there are 13 communication themes regarding the communication experiences of COVID-19 survivors in their neighborhoods, namely: 1) Proper intimacy, 2) Hanging out together, 3) Greeting each other, 4) Using WhatsApp applications, 5) Support, 6) Keeping a distance, 7) Feeling isolated, 8) Unable to communicate directly, 9) Re-acceptance, 10) Relationships are getting closer, 11) Withdrawing, 12) Stigma and negative labels, and 13) Inform self-healing. In addition, this study also illustrates the importance of communication for survivors in informing their recovery.